Diabetic Retinopathy and Associated Risk Factors Among Diabetic Patients Attending Eye Camps In Northern Bangladesh (Journal of Preventive and Social Medicine, 2022)
Background: Diabetic retinopathy (DR) is one of the leading causes of vision loss which occurs as a result of microvascular complication of diabetes. The aim of the study is to assess the prevalence and factors associated with development of diabetic retinopathy among diabetic patients attending eye camps in a diabetic hospital of northern Bangladesh.Methods: This was a population-based cross-sectional study, conducted through five comprehensive eye camps at diabetic association hospital in Nilphamari, Bangladesh. Previously diagnosed patients with Diabetes Mellitus attending eye camps were the sample of this study which included a total of 254 participants. All participants underwent complete eye examination to check for any signs of DR with any other ocular abnormalities. Retinopathy was determined by fundus photography and direct ophthalmoscopy. Participants were also interviewed and examined to determine their demographic characteristics, clinical conditions, awareness on diabetic retinopathy and regularity of their eye visits.Results: A total of 254 subjects were screened for diabetic retinopathy. Of them, 64 (25.2%) had diabetic retinopathy including, including 53 (20.9%) with non-proliferative retinopathy (NPDR) and 11 (4.3%) with proliferative diabetic retinopathy (PDR). Clinically significant macular edema (CSME) was detected in 7 patients (2.7%). The prevalence of diabetic retinopathy was higher among patients with greater duration of diabetes (p=< 0.001), poor glycemic control (p=0.002) and presence of hypertension (p=0.05).Conclusion: Regular screening in patients with diabetes for early detection of diabetic retinopathy by effective screening program and increasing public awareness are highly recommended in Bangladesh.JOPSOM 2021; 40(2):16-25